Polyacrylic-Co-Maleic-Acid-Coated Magnetite Nanoparticles for Enhanced Removal of Heavy Metals from Aqueous Solutions - Mlih, Rawan; Suazo-Hernández, Jonathan; Liang, Yan; Tombácz, Etelka; Bol, Roland; Klumpp, Erwin (Colloids and interfaces, 2023)
The physicochemical properties of ligand-coated nanoparticles make them superior adsorbents for heavy metals from water. In this study, we investigate the adsorption potential of novel polyacrylic-co-maleic-acid-coated magnetite nanoparticles (PAM@MNP) to remove Pb2+ and Cu2+ from an aqueous solution. We argue that modifying the surface of MNP with PAM enhances the physicochemical stability of MNP, improving its ability to remove heavy metals. The adsorption kinetics data show that PAM@MNP attained sorption equilibrium for Pb2+ and Cu2+ after 60 min. The kinetics data are fitted accurately by the pseudo-first-order kinetic model. The calculated Langmuir adsorption capacities are 518.68 mg g−1 and 179.81 mg g−1 for Pb2+ and Cu2+, respectively (2.50 mmol g−1 and 2.82 mmol g−1 for Pb2+ and Cu2+, respectively). The results indicate that PAM@MNP is a very attractive adsorbent for heavy metals and can be applied in water remediation technologies.